The Impact of Increasing PPN Rates on Economic Growth in Indonesia - Susena, Karona Cahya; Hidayah, Nenden Restu; Anggraini, Adinda Dewi (Social Sciences Journal, 2025)
The aim of this research is to explore the effect of VAT on national income. This research aims to find out how VAT can affect Indonesian income and how national income can be influenced by VAT. The research method used in this research is a qualitative method. The qualitative method was chosen because the aim of this research is to understand how VAT affects Indonesian income and how national income is influenced by VAT. The research method used in this research is a qualitative method with a document analysis approach. Value Added Tax (VAT) is an important instrument in a country's fiscal policy, including Indonesia. Careful data analysis and in-depth discussion show that VAT has a positive and significant influence on Indonesian income.